Chapter: 'MOOC Design Workshop: Educational Innovation with Empathy and Intent' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Yishay Mor (Lecture Notes in Computer Science, 2016)
For the last two years we have been running a series of successful MOOC design workshops. These workshops build on previous work in learning design and MOOC design patterns. The aim of these workshops is to aid practitioners in defining and conceptualising educational innovations (predominantly, but not exclusively MOOCs) which are based on an empathic user-centered view of the target learners and teachers. In this paper, we share the main principles, patterns and resources of our workshops and present some initial results for their effectiveness.